Analysis of Cost of Goods Sold Before and After The Issuance of Regulation of the Minister of Finance (PMK) No. 97 / PMK.010 / 2015 In The Metal Industry of Iron and Steel Listed on BEI - Nelli Novyarni; Arini Yuliasih (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2018)
The external factor affecting the basic iron and steel industry in Indonesia is the Regulation of the Minister of Finance of Indonesia concerning the imposition of import duty tariff on imported goods. The purpose of this study is: to determine the difference in cost of goods sold before and after the Minister of Finance Regulation no. 97 / PMK.010 / 2015. This research uses descriptive research type with quantitative, which measured by using comparative method / comparison with SPSS 23,00. The population of this research is sub metal company and the like listed on Indonesia Stock Exchange (IDX) from 3rd Quarter 2014 to 1st Quarter 2016. Samples are determined purpuse sampling method, with the sample number is 11 companies. The data used in this research is secondary data. Technique of collecting data using documentation method through IDX official website: www.idx.co.id. hypothesis testing using Wilcoxon Signed Ranks Test. It is known that the result of the significance level of 0.768> 0.05.So the conclusion is: there is no significant difference in cost of goods sold before and after the Regulation of the Minister of Finance No. 97 / PMK.010 / 2015.